THE EFFECT OF USING MARKETPLACES ON MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) ON COMMUNITY SATISFACTION - Ade Mardiah Hayati; Tata Dibrata; Childan Fauzi (Journal of Business Administration, 2022)
MSMEs in Indonesia reached 62.9 million units consisting of; agriculture, animal husbandry, processing, trade, services and communication. In Indonesia, MSMEs have a strategic role and a major influence on the development of the national economy. Era 4.0, it is as if micro, small and medium enterprises (MSMEs) are required to develop competitiveness through the use of digital platforms, including MSME actors in Bandung City. Utilizing the marketplace is a business strategy in the business world, given the increasingly complex problems, the increasing number of competitors and the demand to always keep abreast of developments in the global world which requires us to always act creatively and innovatively. But behind that, there are also factors that hinder the development of a business, such as the inhibiting factors for the development of a business more specifically, namely the difficulty of obtaining market opportunities and expanding the market. In this study used quantitative research methods. In this research, two mutually influential variables were determined, namely the marketplace (X) and community satisfaction (Y). The hypothesis to be tested in this study relates to whether or not there is a significant influence between the independent or independent variables on the dependent or independent variables. The research results obtained indicate that the marketplace for SMEs will affect community satisfaction. This was produced through the results of the influence test of 11,950 that the marketplace has a significant influence on people's satisfaction